2004
DOI: 10.1177/0091270004265643
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Omeprazole on Bioavailability of Bismuth following Administration of a Triple Capsule of Bismuth Biskalcitrate, Metronidazole, and Tetracycline

Abstract: The objective of this study was to determine the impact of omeprazole on bismuth (Bi) bioavailability when given in a three-in-one capsule containing bismuth biskalcitrate, metronidazole, and tetracycline. Thirty-four healthy volunteers were randomly assigned to receive three capsules (each containing bismuth biskalcitrate 140 mg + metronidazole 125 mg + tetracycline 125 mg) qid alone x 6 days or the same treatment + omeprazole (OM) 20 mg bid. Blood was drawn at intervals for 24 hours after the last dose. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…The doses of bismuth used in H pylori eradication are administered for a much shorter duration, typically 1 to 2 wk. In a recent bioavailability study, where bismuth salts were given in combination with omeprazole for 6 d [12] , plasma levels of bismuth remained well below 50 μg/mL, but a review of their safety profile would provide additional evidence that such low doses of bismuth, given for a short period of time, do not expose patients to undue risks. We have therefore conducted a systematic review and meta-analysis of available published literature to assess the magnitude of the risk of adverse events experienced when bismuth salts are used, either alone or in combination with one or more antibiotics, to eradicate H pylori.…”
Section: Introductionmentioning
confidence: 99%
“…The doses of bismuth used in H pylori eradication are administered for a much shorter duration, typically 1 to 2 wk. In a recent bioavailability study, where bismuth salts were given in combination with omeprazole for 6 d [12] , plasma levels of bismuth remained well below 50 μg/mL, but a review of their safety profile would provide additional evidence that such low doses of bismuth, given for a short period of time, do not expose patients to undue risks. We have therefore conducted a systematic review and meta-analysis of available published literature to assess the magnitude of the risk of adverse events experienced when bismuth salts are used, either alone or in combination with one or more antibiotics, to eradicate H pylori.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Systemic use of Mtz for periodontal treatment has been evaluated in different oral doses: 250 mg, three times/day; [6] 400 mg, three times/day; [7][8][9] and 500 mg, three times/ day. [10,11] Mtz results in excellent oral absorption, [12] and its oral bioavailability (>90%) is commonly reported, [13,14] with tissue concentrations generally similar to or slightly lower than those measured in the serum. [15] The blood serum protein binding is 10-15%.…”
Section: Introductionmentioning
confidence: 88%
“…Right after the first collection, all volunteers had a standard breakfast and water ad libitium. Blood (5 ml) and saliva (3 ml) samples were collected 8,9,12,13,15,19,32 and 56 h after gel application.…”
Section: Gel Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…trointestinal tract and in radiotherapy (Bethge et al 2003;Spenard et al 2004). A thorough examination of extensive research on the toxicity of metals and their salts has demonstrated, however, that it is not prudent to infer human and ecosystem effects across various compounds containing the same metal ion or across different environmental conditions of exposure (Dopp et al 2004).…”
Section: Schoenung Et Al Pb-free Electronics: Policy Differences Anmentioning
confidence: 99%